Occupational therapy with elders : strategies for the COTA - Byers-Connon, Sue, ....-; Lohman, Helene, ....-; Padilla, René L., ....- (St. Louis (Mo.) : Elsevier Mosby, 2004)
This unique resource clearly presents a comprehensive range of elder care strategies and insights for the COTA. Coverage includes important trends, concepts and theories related to aging, as well as professional issues for occupational therapy professionals. A multi-disciplinary approach demonstrates the importance of the collaboration between the Occupational Therapist, Registered (OTR), and COTA.
Keywords: Cerebrovasculair accident -- Ouderen; Ergotherapie -- Ouderen; Geneesmiddelen -- Ouderen; Ouder worden -- Zingeving; Seksualiteit -- Ouderen